Effect of Se addition on optical and electrical properties of chalcogenide CdSSe thin films - Hassanien, A.S.; Akl, Alaa A. (Superlattices and microstructures, 2016)
Compositional dependence of optical and electrical properties of chalcogenide CdSxSe1−x (0.4≥x≥0.0 at. %) thin films was studied. Cadmium sulphoselenide films were deposited by thermal evaporation technique at vacuum (8.2×10−4 Pa) onto preheated glass substrates (523 K). The evaporation rate and film thickness were kept constant at 2.50 nm/s and 375 ± 5 nm, respectively. X-ray diffractograms showed that, the deposited films have the low crystalline nature. Energy dispersive analysis by X-ray (EDAX) was used to check the compositional elements of deposited films. The absorption coefficient was determined from transmission and reflection measurements at room temperature in the wavelength range 300–2500 nm. Optical density, skin depth, optical energy gap and Urbach's parameters of CdSSe thin films have also been estimated. The direct optical energy gap decreased from 2.248 eV to 1.749 eV when the ratio of Se-content was increased from 0.60 to 1.00 . Conduction band and valance band positions were evaluated. The temperature dependence of dc-electrical resistivity in the temperature range (293–450 K) has been reported. Three conduction regions due to different conduction mechanisms were detected. Electrical sheet resistance, activation energy and pre-exponential parameters were discussed. The estimated values of optical and electrical parameters were strongly dependent upon the Se-content in CdSSe matrix. The Position of valance and conduction bands of thin films of CdSxSe1−x system. [Display omitted] •Influence of Se on optical and electrical properties of CdSSe thin films was studied.•New data of some optical and electrical parameters were estimated and discussed.•Optical density, Skin depth, Urbach parameters, CB and VB positions were evaluated.•Rsh, bulk resistivity, conduction mechanisms and activation energies were discussed.•Results indicate that CdSSe thin films are useful for photovoltaic applications.